DFID Time Complexity in Mobile Network - Justin Sophia, I; Rama, N (International Journal of Computer Sciences and Engineering, 2025)
Hexagonal network structures the base for mobile communication networks. To increase the efficiency of mobile communication, we implement the DFID algorithm for transmission. Let DFID denote the time taken by DFS and BFS preorder traversing to find the vertex x in graph DFID(x,G). In this section we discuss DFS and BFS for G beign a hexagonal mesh of dimension n i.e HXn..Thereby computing the time complexity of DFID algorithm for mobile networking.